2016
DOI: 10.1128/jcm.02492-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an IgG Enzyme-Linked Immunosorbent Assay as a Serological Assay for Detection of Mycoplasma bovis Infection in Feedlot Cattle

Abstract: dMycoplasma bovis is a pathogen of emerging significance in cattle throughout the world that is causing a range of diseases, including mastitis, arthritis, and pneumonia. The limited availability and efficacy of current diagnostic and prophylactic tools for its control and its increasing antimicrobial resistance are contributing to its increasing importance in beef and dairy cattle. We have developed an indirect IgG enzyme-linked immunosorbent assay (ELISA) based on a recombinant fragment of the MilA protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 21 publications
4
54
0
1
Order By: Relevance
“…The low coefficient of determination value and weaker association in the current study may have been due, in part, to imperfect specificity of the ELISA in Australian dairy production systems. Although the specificity of this ELISA was high when used on individual serum samples from nonexposed calves (Wawegama et al, 2016), we observed seroprevalences in lactating cows varying from 6 to 22% in the 6 control herds with no known clinical history of mycoplasmosis. This may have been attributable to antigen cross-reactivity with other pathogens.…”
Section: Itemmentioning
confidence: 69%
See 2 more Smart Citations
“…The low coefficient of determination value and weaker association in the current study may have been due, in part, to imperfect specificity of the ELISA in Australian dairy production systems. Although the specificity of this ELISA was high when used on individual serum samples from nonexposed calves (Wawegama et al, 2016), we observed seroprevalences in lactating cows varying from 6 to 22% in the 6 control herds with no known clinical history of mycoplasmosis. This may have been attributable to antigen cross-reactivity with other pathogens.…”
Section: Itemmentioning
confidence: 69%
“…Finally, the absence of a close association may have been partly attributable to poor sensitivity of the Bio-X ELISA at the individual animal level. Sensitivity of this ELISA has been estimated as 37% (95% CI: 22-54) relative to an IgG ELISA in sera from individual animals (Wawegama et al, 2016) and 60% (95% posterior credibility interval: 38-96) in BTM (Nielsen et al, 2015). However, although not all herds with a known history of M. bovis disease had a positive BTM (≥37 ODC %), the BTM ELISA may be more useful in identifying absence or presence of previous exposure to M. bovis at the herd level.…”
Section: Itemmentioning
confidence: 99%
See 1 more Smart Citation
“…As M. bovis can be detected from body sites other than the mammary gland, such purchases pose a risk for the introduction of M. bovis. More recently, studies have evaluated the use of ELISA to detect animals previously exposed to M. bovis (and hence, potentially infected; Wawegama et al, 2016).…”
mentioning
confidence: 99%
“…Suggestions of poor sensitivity 63,115 Organism must be viable, therefore storage and handling of the sample is important 7,11 Animal must be shedding the organism at the time of sampling 26,28 Abbreviation: PCR, polymerase chain reaction.…”
Section: Identification Of Non-viable Organisms May Lead To Insignifimentioning
confidence: 99%